LEXICAL AND SEMANTIC FEATURES OF THE CONCEPT "HAPPINESS" IN UZBEK AND ENGLISH - Karimova S (Galaxy International Interdisciplinary Research Journal, 2021)
The language itself embodies the cultural and national mentality of the people. Every owner of a language preserves its culture, and therefore language signs have the character of performing the function of cultural symbols and thus serve as a means of expressing the main cultural relationship.